Pengaruh Kepemimpinan dan Motivasi Kerja terhadap Disiplin Kerja Pegawai Kantor Pengadilan Negeri Mataram - Ratu Ulia; Sri Wahyulina; Armi Sulthon Fauzi (Universitas 45 Surabaya, 2024)
This research is entitled The Influence of Leadership and Work Motivation on the Work Discipline of Mataram District Court Office Employees. Aims to determine the influence of leadership and work motivation on employee work discipline. The type of research used is causal associative research. The data collection method used in this research is the census method. The population and respondents in this study were all 78 Mataram District Court employees. The data analysis tool used is Multiple Linear Regression using IBM SPSS version 26. The instrument tests used in this research are validity and reliability tests. The classic assumption tests used in this research are the normality test, multicollinearity test and heteroscedasticity test. Furthermore, the hypothesis tests used in this research are the F test, t test and coefficient of determination. The results of the analysis show that: (1) Leadership has a positive and significant effect on Work Discipline at the Mataram District Court Office (2) Work Motivation has a positive and significant effect on Work Discipline at the Mataram District Court Office.